A controversial cover - Barrett, Lorna (Barrett, Lorna. Booktown mystery, 2024)
"Tricia Miles is ready to close the book on all her amateur sleuthing - she's tired of finding dead bodies and being accused of murder. But even the best laid plans often go awry. Stoneham is all abuzz when Lauren Barker, a famous children's book author, arrives for an event at the local library. Lauren is a Stoneham native, and her new book strikes some members of the town as controversial. But when Lauren is found strangled to death after an altercation at the event, the plot twist throws Tricia right back into the middle of things. Who could possibly have wanted Lauren dead? Was it Dan Reed, who had to be thrown out of the signing for spouting conspiracy theories and causing a disturbance? Stella Kraft, Lauren's high school teacher, who thought of the author as a protégé-something Lauren violently disputed? Or the mystery man who spoke to Lauren just before she was found dead? With the suspect count climbing higher and more information about Lauren's past coming to light, will Tricia be able to give this story a happily ever after?"--